Aerobiology of the Asian soybean rust pathogen for monitoring inoculum dispersal and RT qPCR detection of the SdhC I86F substitution associated with resistance to SDHI fungicides in populations of Phakopsora pachyrhizi from Brazil - Krug, Loane Dantas [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Asian soybean rust, caused by the fungus Phakopsora pachyrhizi (Pp), is the main disease affecting soybean production in Brazil, leading to significant losses and management costs estimated at approximately US$ 2 billion per crop. Since its introduction to Brazil in the 2001/2002 growing season, the disease has spread rapidly, affecting nearly all soybean-producing regions and consistently challenging farmers. The widespread resistance of the pathogen to fungicides, particularly to QoI, DMI, and SDHI groups, has compromised chemical control, necessitating new management strategies. This study focused on monitoring airborne populations of P. pachyrhizi in Londrina, Paraná, between 2019 and 2021, using a high-volume cyclone for air collection and quantitative real-time PCR (qPCR) for pathogen DNA detection. Sample analysis revealed the presence of P. pachyrhizi in 24.73% of samples, with significant peaks in March 2020 and 2021, coinciding with the critical grain-filling period. Climate variables, such as rainfall, relative humidity, and wind speed, showed significant correlations with the presence of pathogen DNA, with accumulated rainfall presenting a negative correlation, and relative humidity and wind speed showing positive correlations at certain periods. Furthermore, fungicide resistance has become an increasing concern. Resistance to QoI and DMI fungicides has reduced the efficacy of chemical control, while new SDHI fungicides have also faced resistance. The detection of the SdhC-I86F mutation, associated with SDHI resistance, was prevalent in populations sampled between 2020/21 and 2022/23 across various Brazilian states, confirming the persistence of this substitution. The analyses also showed that phenotyped populations had reduced sensitivity to the fungicide fluxapyroxad. The results highlight the effectiveness of the employed methodology for monitoring and detecting P. pachyrhizi and provide valuable information for more efficient management practices, which may help reduce dependence on fungicides and promote more sustainable agriculture.

A ferrugem asiática da soja, causada pelo fungo Phakopsora pachyrhizi (Pp), é a principal doença que afeta a produção de soja no Brasil, gerando perdas significativas e custos de manejo estimados em aproximadamente 2 bilhões de dólares por safra. Desde sua introdução no Brasil na safra 2001/2002, a doença se espalhou rapidamente, atingindo praticamente todas as regiões produtoras e desafiando constantemente os agricultores. A resistência generalizada do patógeno a fungicidas, particularmente aos grupos QoI, DMI e SDHI, tem comprometido o controle químico, exigindo novas estratégias de manejo. Este estudo focou no monitoramento das populações aéreas de P. pachyrhizi em Londrina, Paraná, entre 2019 e 2021, utilizando um ciclone de alto volume para coleta de ar e PCR quantitativo em tempo real (qPCR) para detecção de DNA do patógeno. A análise das amostras revelou a presença de P. pachyrhizi em 24,73% das amostras, com picos significativos em março de 2020 e 2021, coincidentes com o período crítico de enchimento de grãos. As variáveis climáticas, como precipitação, umidade relativa e velocidade do vento, mostraram correlações significativas com a presença de DNA do patógeno, com a precipitação acumulada apresentando uma correlação negativa, e a umidade relativa e a velocidade do vento mostrando correlações positivas em determinados períodos. Além disso, a resistência a fungicidas tem sido uma preocupação crescente. A resistência a fungicidas QoI e DMI diminuiu a eficácia do controle químico, enquanto novos fungicidas SDHI também enfrentaram resistência. A detecção da mutação SdhC-I86F, associada à resistência a SDHI, foi prevalente em populações amostradas entre 2020/21 e 2022/23 em diferentes estados brasileiros, confirmando a persistência desta substituição. As análises também mostraram que as populações fenotipadas tinham sensibilidade reduzida ao fungicida fluxapiroxade. Os resultados destacam a eficácia da metodologia empregada para monitoramento e detecção de P. pachyrhizi e fornecem informações valiosas para práticas de manejo mais eficientes, que podem ajudar a reduzir a dependência de fungicidas e promover uma agricultura mais sustentável.
Aerobiologia do patógeno da ferrugem asiática da soja para monitoramento da dispersão de inóculo e detecção por RT qPCR da substituição SdhC I86F associada à resistência a fungicidas SDHI em populações de Phakopsora pachyrhizi do Brasil
Keywords: Pathogen monitoring; Inoculum dispersal; Molecular detection; Fungal DNA quantification; Environmental conditions; Smart disease management strategies; Phakopsora pachyrhizi; SdhC-I86F substitution; Fluxapyroxad; Succinate dehydrogenase inhibitor; Monitoramento de patógenos; Dispersão de inóculo; Detecção molecular; Quantificação de DNA fúngico; Condições ambientais; Estratégias inteligentes de manejo de doenças; Substituição SdhC-I86F; Fluxapiroxade; Inibidores da succinato desidrogenase